Comparison of Control Configurations and MPPT Algorithms for Single-Phase Grid-Connected Photovoltaic Inverter - PRASATSAP, U.; NERNCHAD, N.; TERMRITTHIKUN, C.; SRITA, S.; KAEWCHUM, T.; SOMKUN, S. (Advances in Electrical and Computer Engineering, 2023)
This paper presents studies of the four maximum power point tracking (MPPT) algorithms of a single-phase grid-connected photovoltaic (PV) inverter based on single loop voltage control (VC) and cascaded voltage and current control (CVCC). The purpose of this research was to evaluate four techniques for maximum power tracking control: (1) the Perturbation and Observation (P&O) MPPT&VC, (2) the Incremental Conductance (InC) MPPT&VC, (3) the P&O MPPT&CVCC and (4) the InC MPPT&CVCC. The MPPT efficiency values of each technique were affected by sudden changes in various irradiances. The CVCC was found to reduce the oscillating PV power and have a faster response time of MPPT from the PV array than the VC configuration. The InC MPPT&CVCC technique can track maximum power when irradiance changes rapidly. The simulation results showed that the InC MPPT&CVCC technique can decrease oscillation at a steady state around the set point and has a fast response time of MPPT, reduced electrical power ripple, and less power loss. The average efficiency of MPPT was 99.98%.